Immunogold Labeling for Scanning Electron Microscopy - Goldberg, Martin W; Fišerová, Jindřiška (Methods in molecular biology (Clifton, N.J.), 2016)
Scanning electron microscopes are useful biological tools that can be used to image the surface of whole organisms, tissues, cells, cellular components, and macromolecules. Processes and structures that exist at surfaces can be imaged in pseudo, or real 3D at magnifications ranging from about 10× to 1,000,000×. Therefore a whole multicellular organism, such as a fly, or a single protein embedded in one of its cell membranes can be visualized. In order to identify that protein at high resolution, or to see and quantify its distribution at lower magnifications, samples can be labeled with antibodies. Any surface that can be exposed can potentially be studied in this way. Presented here is a generic method for immunogold labeling for scanning electron microscopy, using two examples of specimens: isolated nuclear envelopes and the cytoskeleton of mammalian culture cells. Various parameters for sample preparation, fixation, immunogold labeling, drying, metal coating, and imaging are discussed so that the best immunogold scanning electron microscopy results can be obtained from different types of specimens.
Keywords: buněčná membrána; epoxidové pryskyřice; Tissue Embedding; Tissue Fixation; koloidní zlato; jaderný obal; formaldehyd; exprese genu; cytoskelet; antigeny; Gene Expression; Xenopus laevis; Gold Colloid; zalévání tkání; Microtomy; Nuclear Pore Complex Proteins; Female; Microscopy, Electron, Scanning; Envelope; Antigens; Xenopus; zvířata; Immunohistochemistry; imunohistochemie; barvení a značení; oocyty; polymery; Immunogold; Polymers; ženské pohlaví; mikrotomie; Nuclear; protilátky; mikroskopie elektronová rastrovací; fixativa; fixace tkání; Labeling; Scanning electron microscopy; Antibodies; komplex proteinů jaderného póru; Nuclear Envelope; Epoxy Resins; Animals; Cell Membrane; Fixatives; Oocytes; Cytoskeleton; Formaldehyde; Staining and Labeling